Making agriculture work for nutrition - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
IFPRI’s research has changed the way the international development community thinks about the links between agriculture and nutrition, and highlights the syner¬gies with health, education, gender, and social protection that can improve poor people’s health and nutrition.